Investigating the extent to which students share tacit knowledge using moblie phones in group projects - Khumbula, Chiedza (Department of Information Systems, 2015)
The benefit of group-learning to enhance the sharing of knowledge among students in group projects is increasingly preferred over traditional methods. However, there are still many challenges facing students learning in groups. These include: lack of leadership, time and scheduling of workload, free riding, individual and social barriers, lack of team development, lack of social interaction, lack of motivation, inadequate rewards, skills and attitude problems or social loafing. The integration of the mobile context and technologies in group-learning can assist in minimizing some of these barriers. Information Communication Technologies (ICTs) are believed to transform teaching and learning processes through the facilitation of communication and interaction among teachers and learners. Researchers have also found that tacit knowledge has much greater importance to industry and academia. For instance, it allows individuals to achieve goals they personally value. It can be used to measure or predict job performance and those possessing it have been found to manage themselves and others better. This research investigates the extent to which students share tacit knowledge using the mobile phone in group projects, and examines if they achieve better performance with this technology.